Klotho expression in long bones regulates FGF23 production during renal failure. Issue 5 (9th February 2017) - Kaludjerovic, Jovana; Komaba, Hirotaka; Sato, Tadatoshi; Erben, Reinhold G.; Baron, Roland; Olauson, Hannes; Larsson, Tobias E.; Lanske, Beate
ABSTRACT: Circulating levels of bone‐derived fibroblast growth factor 23 (FGF23) increase early during acute and chronic kidney disease and are associated with adverse outcomes. Membrane‐bound Klotho acts as a permissive coreceptor for FGF23, and its expression was recently found in osteoblasts/osteocytes. We hypothesized that Klotho in bone cells is part of an autocrine feedback loop that regulates FGF23 expression during renal failure. Thus, we induced renal failure in mice with targeted deletion of Klotho in long bones. Uremic wild‐type (KL fl/fl ) and knockout (Prx1‐Cre;KL fl/fl ) mice both responded with reduced body weight, kidney atrophy, hyperphosphatemia, and increased bone turnover. Importantly, long bones of Prx1‐Cre;KL fl/fl mice but not their axial skeleton failed to increase FGF23 expression as observed in uremic KL fl/fl mice. Consequently, Prx1‐Cre;KL fl/fl mice had significantly lower serum FGF23 and parathyroid hormone levels, and higher renal 1‐α‐hydroxylase expression, serum 1, 25‐dihydroxyvitamin D, and calcium levels than KL fl/fl mice. These results were confirmed in two independent models of renal failure, adenine diet induced and 5/6 nephrectomy. Moreover, FGF23‐treated bone cells required Klotho to increase FGF23 mRNA and ERK phosphorylation. In summary, our novel findings show that Klotho in bone is crucial for inducing FGF23 production upon renal failure. We propose the presence of an autocrine feedback loop in which Klotho senses the need for FGF23.—Kaludjerovic, J., Komaba, H., Sato, T., Erben, R. G., Baron, R., Olauson, H., Larsson, T. E., Lanske, B. Klotho expression in long bones regulates FGF23 production during renal failure. FASEB J. 31, 2050–2064 (2017). www.fasebj.org